Treatment of beef with gaseous ozone: Physicochemical aspects and antimicrobial effects on heterotrophic microflora and listeria monocytogenes. (March 2021) - Giménez, Belén; Graiver, Natalia; Giannuzzi, Leda; Zaritzky, Noemí
Abstract: The treatment of beef with gaseous ozone (GO) was analyzed and the physicochemical characteristics (texture, lipid oxidation, surface color) and food safety (microbial growth of heterotrophic microflora and inoculated Listeria monocytogenes ) were evaluated. Transient changes in ozone concentration within the chamber were mathematically modeled using a non-stationary mass balance. Ozone pulses were applied and treatment intensities were evaluated in each case. GO treatment prolonged refrigerated storage of vacuum packed beef. Long periods of exposure to ozone (>10 min) negatively affected the red color and oxidative rancidity. The most effective treatments to control microbial flora were ozone pulses ranging between 5 and 10 min duration every 30 min for 5 h using 280 mg O3 m −3 ; these treatments allowed the reduction of more than 1 logarithmic cycle the counts of the natural flora in beef (lactic acid bacteria, mesophilic and enterobacteriaceae), maintaining oxidative stability and adequate physicochemical parameters. Additionally these low doses of GO decreased the counts of inoculated L. monocytogenes (10 2 CFU g tissue −1 ) to values below the detection limit for 16 days at 4 °C limiting its growth during refrigerated storage. The use of GO in beef products allows the control of microbial growth during refrigerated storage maintaining high quality parameters. Graphical abstract: Image 1 Highlights: Gaseous ozone (GO) prolonged beef refrigerated storage life keeping quality. GO pulses (280 mg O3 m −3 ) 5–10 min duration every 30 min for 5 h were efficient. GO (218–283 mg O3 m −3 ) decreased 1.5 log cycles heterotrophic counts in sliced beef. GO treatment decreased inoculated L. monocytogenes counts by more than 1 log cycle. Exposure times to GO (>10 min) negatively affected beef red color and rancidity.